Strategi pengembangan Usaha Mikro Kecil Menengah (UMKM) di Kota Malang melalui literasi informasi - Muhammad Shobaruddin (Jurnal Kajian Informasi dan Perpustakaan, 2020)
This study examined Micro, Small, and Medium Enterprises (MSMEs) development strategies through information literacy. Information literacy can be interpreted as expertise in effectively accessing and evaluating information to solve problems and make decisions. This study aimed to improve the quality of human resources driving MSMEs in Malang through information literacy. Descriptive qualitative methods were used to describe the phenomenon as a whole. Data were collected through Focus Group Discussions (FGDs) to determine the pattern of problem identification, searching and implementing solutions, and applying information literacy to the UMKM process in Malang City. The FCD results were analyzed by identifying problems, solutions that were implemented, and information literacy application. The next step was to formulate the stages of the MSME development strategy. MSMEs in Malang City faced internal (capital, human resources, and infrastructure) and external (government support, community roles, and consumer response) constraints. The solutions implemented to overcome these obstacles have not thoroughly utilized information literacy skills, so the problem recurs. MSME development strategies that can be applied with third parties' assistance are problem identification, reflection on applied solutions, and development of information literacy skills (the ability to access information, sort and select, and understand and implement it). Based on these findings, the role of third parties, such as the government and the research team, is quite important for implementing strategies and improving the quality of MSME Human Resources.